2015
DOI: 10.1007/s13213-015-1129-7
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacilli possess inhibitory activity against dipeptidyl peptidase-4 (DPP-4)

Abstract: Dipeptidyl peptidase-4 (DPP-4) plays an important role in the enzymatic inactivation of incretin hormones. In this context, drugs that inhibit DPP-4 have been developed and clinically approved as therapies for type 2 diabetes. As the primary substrates of DPP-4 are produced in the intestinal lining, we investigated whether lactobacilli colonizing the gut could inhibit this enzyme. Fifteen Lactobacillus strains (Lb 1-15) from human infant faecal samples were isolated, identified, extracted and screened for inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
1
18
0
1
Order By: Relevance
“…NC, normal control group; DC, diabetic control group; LG, DC plus L. rhamnosus GG; LA, DC plus L. acidophilus KLDS1.0901. activity with L. acidophilus KLDS1.1003 and L. acidophilus KLDS1.0901, which was consistent with other studies (Panwar et al, 2015;Zhu et al, 2016). However, it was observed that DPP-IV inhibitory levels were higher in previous studies; this may be due to different concentrations of bacteria or sources of DPP-IV.…”
Section: Discussionsupporting
confidence: 93%
“…NC, normal control group; DC, diabetic control group; LG, DC plus L. rhamnosus GG; LA, DC plus L. acidophilus KLDS1.0901. activity with L. acidophilus KLDS1.1003 and L. acidophilus KLDS1.0901, which was consistent with other studies (Panwar et al, 2015;Zhu et al, 2016). However, it was observed that DPP-IV inhibitory levels were higher in previous studies; this may be due to different concentrations of bacteria or sources of DPP-IV.…”
Section: Discussionsupporting
confidence: 93%
“…Based on these, Yun et al [ 49 ] speculated that LAB in breast milk could be one of the important ingredients present for the prevention of diabetes and thus recommended further studies on this. In another study by Panwar et al [ 54 ], some LAB strains ( L. rhamnosus, L. plantarum, L. johnsonii, L. acidophilus and L. casei ) were able to stimulate the secretion of gut hormones GLP-1 and GIP which play a key role in modulating insulin secretion and inhibition of DPP IV. This study showed that probiotic LABs may be used as modulators of incretin hormones which can be explored as potential bio-therapeutics against diabetes.…”
Section: Probiotic Lab and Type-2 Diabetes Treatmentmentioning
confidence: 99%
“… [ 57 ] Lactobacillus spp Significant DPP-IV inhibitory activity, this varied among the strains studied. [ 54 ] Lactobacillus sakei OK67 Inhibition of HFD-induced body and epididymal fat weight gain, HFD-induced TNF-α and IL-ß expression. Inhibition of NF-kB activation in the colon.…”
Section: Probiotic Lab and Type-2 Diabetes Treatmentmentioning
confidence: 99%
“…diarrhea, inflammatory bowel disease, obesity, type 2 diabetes, cardiovascular disease, cancer etc. ( Mallappa et al, 2012 ; Panwar et al, 2014 , 2016 ; Ranji et al, 2015 ). It has been clearly understood that the gut inhabitants and their proper balance is the foremost criteria that determines healthy status, particularly in terms of metabolic disorders ( Wang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%